Commiphora myrrha n-hexane extract suppressed breast cancer progression through induction of G0/G1 phase arrest and apoptotic cell death by inhibiting the Cyclin D1/CDK4-Rb signaling pathway - Huang, Huiming; Xie, Jinxin; Wang, Fei; Jiao, Shungang; Li, Xingxing; Wang, Longyan; Liu, Dongxiao; Wang, Chaochao; Wei, Xuejiao; Tan, Peng; Tu, Pengfei; Li, Jun; et al. (Frontiers in Pharmacology, 2024)
Background: Breast cancer (BC) is one of the most frequently observed malignancies globally, yet drug development for BC has been encountering escalating challenges. Commiphora myrrha is derived from the dried resin of Commiphora myrrha (T. Nees) Engl., and is widely adopted in China for treating BC. However, the anti-BC effect and underlying mechanism of Commiphora myrrha remain largely unclear. Methods: MTT, EdU assay, and colony formation were used to determine the effect of Commiphora myrrha n-hexane extract (CMHE) on the proliferation of human BC cells. Cell cycle distribution and apoptosis were assessed via flow cytometry analysis. Moreover, metastatic potential was evaluated using wound-scratch assay and matrigel invasion assay. The 4T1 breast cancer-bearing mouse model was established to evaluate the anti-BC efficacy of CMHE in vivo. RNA-sequencing analysis, qRT-PCR, immunoblotting, immunohistochemical analysis, RNA interference, and database analysis were conducted to uncover the underlying mechanism of the anti-BC effect of CMHE. Results: We demonstrated the significant inhibition in the proliferative capability of BC cell lines MDA-MB-231 and MCF-7 by CMHE. Moreover, CMHE-induced G0/G1 phase arrest and apoptosis of the above two BC cell lines were also observed. CMHE dramatically repressed the metastatic potential of these two cells in vitro. Additionally, the administration of CMHE remarkably suppressed tumor growth in 4T1 tumor–bearing mice. No obvious toxic or side effects of CMHE administration in mice were noted. Furthermore, immunohistochemical analysis demonstrated that CMHE treatment inhibited the proliferative and metastatic abilities of cancer cells, while also promoting apoptosis in the tumor tissues of mice. Based on RNA sequencing analysis, qRT-PCR, immunoblotting, and IHC assay, the administration of CMHE downregulated Cyclin D1/CDK4-Rb signaling pathway in BC. Furthermore, RNA interference assay and database analysis showed that downregulated Cyclin D1/CDK4 signaling cascade participated in the anti-BC activity of CMHE. Conclusion: CMHE treatment resulted in the suppression of BC cell growth through the stimulation of cell cycle arrest at the G0/G1 phase and the induction of apoptotic cell death via the inhibition of the Cyclin D1/CDK4-Rb pathway, thereby enhancing the anti-BC effect of CMHE. CMHE has potential anti-BC effects, particularly in those harboring aberrant activation of Cyclin D1/CDK4-Rb signaling.